PENGARUH PERTUMBUHAN LABA DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Setiani, Frisca Rini; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purposes of this research i.e.: (1) the positive influence of the profit growth to the firm value (2) the positive influence of Corporate Social Responsibility (CSR) to the firm value. The samples are food and beverages companies which are listed in Indonesia Stock Exchange for 3 years of the observation period (2011-2013). The samples have been collected by using purposive sampling. The samples are 9 companies which have been fulfilled the criteria as the research samples. The multiple linear regressions analysis is used as the data analysis instrument. The result of this research shows: (1) the profit growth does not have any significant influence to the firm value. When the profit growth which has been obtained by the company decreases it does not mean that the performance of the company decreases as well. These matters make the investors trust to the company so that the firm value stay high even though the profit growth decreases. (2) the disclosure of Corporate Social Responsibility (CSR) has significant influence to the firm value. Based on the result of the research, the average of the enhancement level of the Corporate Social Responsibility disclosure every year is followed by the enhancement of the firm value.Keywords: Profit Growth, Corporate Social Responsibility (CSR), Firm Value